Reconhecimento dos territórios pesqueiros da comunidade de Espírito Santo do Tauá, Santo Antônio do Tauá, nordeste paraense - BARBOSA, Ana Laide Soares (2021)
The Plan of Action presented here is the consolidation between the conclusion of the Course on Ethnodevelopment and the continuation of the demands that arose during the Tempo Comunidades (TC) of the fishermen and fisherwomen from the fishing community of Vila do Espírito Santo do Tauá, municipality of Santo Antônio do Tauá / Pará, Amazonian coast. It aims to produce elements, through the scheduled activities, to present a dossier on the traditional fishing territory aiming at its recognition. We will seek to highlight the traditional, theoretical and practical knowledge in this construction process aiming at understanding the concept of fishing territory in this community, in a dialogue of knowledge. This is what is intended in this work. It will be a challenge to follow it in the middle of a pandemic, but it is a favorable time to deepen the relevance that is placed in this plan. On one hand, the concept of territory based on an economy of exploitation of natural, oil, mining and accumulation goods; on the other, the construction of territories through traditional practices and knowledge, established from ancestral knowledge. Involving institutional bodies for inspection and environmental management, human rights, academy and civil society is a premise for the viability of the ethnodevelopment plan on the community.